Maintaining Relationship Through Magibung Local Wisdom - I Ketut Sudarsana; I Nyoman Ananda; Ni Nengah Selasih; I Made Suta; Ni Gusti Ayu Agung Nerawati (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2020)
AbstractThe purpose of this study was to find the role of magibung in maintaining community relationships. The implementation of magibung in the belief system is one form of local wisdom in the middle of the Hindu community, especially in Bali. Magibung which is supported by the community through religious ceremonies is one way to strengthen relationships in the Hindu community. It does not only has an impact on the successful implementation of religious ceremonies but also unity and foster